2003
DOI: 10.1001/archotol.129.10.1073
|View full text |Cite
|
Sign up to set email alerts
|

Professional Diversity and Personal Commitments of Pediatric Otolaryngologists

Abstract: Pediatric otolaryngologists participate in many activities beyond clinical medicine. While most considered their time demands to be too busy, few anticipated a change in their activities. This may be reflective of a high level of job satisfaction, financial constraints, or the relative youth of the subspecialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…46 Even for those positions that are filled, pediatric subspecialists in fields such as child and adolescent psychiatry, pediatric otolaryngology, and pediatric surgery have identified that they are too busy to satisfy patient demand for services. [47][48][49] In pediatric emergency medicine and pediatric critical care medicine, for example, the heavy workload and long hours have led to high stress and burnout. For these reasons, a significant number of physicians reported leaving both of these subspecialties, which, over time, could adversely impact workforce supply and constrain access to pediatric subspecialty services.…”
Section: Supply Of the Pediatric Subspecialist Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…46 Even for those positions that are filled, pediatric subspecialists in fields such as child and adolescent psychiatry, pediatric otolaryngology, and pediatric surgery have identified that they are too busy to satisfy patient demand for services. [47][48][49] In pediatric emergency medicine and pediatric critical care medicine, for example, the heavy workload and long hours have led to high stress and burnout. For these reasons, a significant number of physicians reported leaving both of these subspecialties, which, over time, could adversely impact workforce supply and constrain access to pediatric subspecialty services.…”
Section: Supply Of the Pediatric Subspecialist Workforcementioning
confidence: 99%
“…These activities, although critical to increasing medical knowledge and improving the health of patients, limits the ability of these physicians to provide clinical care to pediatric patients. 20,48,53 Other indicators of undersupply are provided by evidence of barriers to accessing pediatric subspecialty care. Of course, the geographic maldistribution of physicians remains a significant barrier.…”
Section: Supply Of the Pediatric Subspecialist Workforcementioning
confidence: 99%
“…Because otolaryngology communities are small, comparative effectiveness research often requires multi‐institutional collaboration to attain analytic sample sizes. Such collaboratives are increasingly common, thereby conferring significant opportunity to disseminate best practices, encourage multidisciplinary collaboration, and improve care 12‐19 . Formation of research consortia suggests a cultural trend toward collaborative dissemination of new information.…”
mentioning
confidence: 99%
“…Such collaboratives are increasingly common, thereby conferring significant opportunity to disseminate best practices, encourage multidisciplinary collaboration, and improve care. [12][13][14][15][16][17][18][19] Formation of research consortia suggests a cultural trend toward collaborative dissemination of new information. However, little research describes how subspecialty surgeons adopt new procedures and whether they decide to sustain those changes.…”
mentioning
confidence: 99%